Anisakids survival after microwaving, freezing and salting fish from Argentina - Lanfranchi, Ana Laura (2010)
Some studies support the effectiveness in controlling nematodes in fishes for human consumption by freezing at -20̈C and by cooking at 74̈C by microwave process. The aim of this work was to analyse the effect of different treatments over anisakids from Argentinean fishes. The known anisakids in fishes from Argentina belong to genera Hysterothylacium, Terranova, Anisakis, Contracaecum and Pseudoterranova, being the three latest recognised as pathogens for human. Living larvae of anisakids obtained from fishes were used for survival assessment. Some parasites were kept in NaCI (0.85%) at 4-5.5°C until death. Anisakis, Terranova, Pseudoterranova, Contracaecum and Hysterothylacium survived during 330, 75, 75, 210 and 90 days, respectively. For freezing, microwaving and salting treatments, infected fillets were exposed at-20̈C until 24 hours, 1 minute at 64.05̈C and 75.56̈C and to salt during 24 hours, respectively. No surviving anisakids were observed neither after freezing nor salting. Anisakis sp. survived at 64.05̈C.